The Social Status of a Teacher in Selected School Policy Programme documents in the Slovak Republic - Plavčan, Peter
Selected findings on financing of education and teachers' salaries based on program documents of school policy: National Programme of Education Project Constantine from 1994, National Programme of Education in the Slovak Republic for the next 15 to 20 Years Millenium from 2002 and the National Programme for the Development od Education for the Years 2018-2027 Learning Slovakia from 2017.